ChemInform Abstract: One‐Pot Transformation of Ph2P(O)‐Protected Ethynes: Deprotection Followed by Transition Metal‐Catalyzed Coupling. Issue 23 (10th June 2014) - Peng, Lifen; Xu, Feng; Suzuma, Yoshinori; Orita, Akihiro; Otera, Junzo
Abstract Ph2P(O) is found to be a useful protecting group for ethynes.